Chlorophyll indexes and gas exchanges of Talisia esculenta seedlings in organic substrates and biofertilizer - Cavalcante, Adailza Guilherme; Cavalcante, Alian Cássio Pereira; Henrique, Josinaldo da Silva; Dantas, Murielle Magda Medeiros; Zuza, José Flávio Cardozo; Araújo, Raunira da Costa (Scientia Plena, 2020)
The Talisia esculenta (popularly called Talisia esculenta) is a native plant from Brazil with great socioeconomic importance regarding its extraction cultivation, however only a few scientific studies were carried out with this species, especially concerning its physiological characteristics. The aim of the present study was to evaluate the utilization of different organic substrates and biofertilizers through the soil on the physiological performance of T. esculenta seedlings. The experiment was performed between August and November 2015. The trial design consisted of randomized blocks, with a factorial arrangement 4 x 2 corresponding to four substrates (Test: control group; SE: commercial substrate; RFV: compost of fruit and vegetable remains; RPI: substrate with remains of industrialized food), in both presence and absence of biofertilizer, with five replicates. The analyzed variables were chlorophyll indexes a, b and gas exchanges. The chlorophyll rates a, b and total were higher on SE, RFV and RPI, but no influences of the biofertilizer were detected on the chlorophyll indexes of T. esculenta seedlings. All substrates (SE, RFV and RPI) increased the chlorophyll indexes a, b and total of the seedlings. The substrates increases the chlorophyll a, b and total indices, except for the control substrate independent of the application of biofertilizer. The efficiency of gas exchange increases with the addition of biofertilizer.